Optimization of stocking density in intensification of mud crab Scylla serrata cultivation in the resirculation system - Yuni Puji Hastuti; Kukuh Nirmala; Iman Rusmana; Ridwan Affandi; Wahyu Budi Kuntari (Jurnal Akuakultur Indonesia)
ABSTRACT